Environmental significance of the Doha Declaration - Charnovitz, Steve (2001)
Notes that the Declaration designates environment as an agency item in the new trade round. Indicates that the ministers are encouraging efforts to promote cooperation between the WTO, the UN Environment Programme (UNEP), and other international, environmental and development organizations.